Contextualising empowerment: highlighting key elements from women's stories of empowerment. Issue 8 (17th November 2019) - Muchtar, Adinda Tenriangke; Overton, John; Palomino-Schalscha, Marcela
ABSTRACT: This article explores key elements of women's empowerment based on findings from fieldwork in South Sulawesi, Indonesia. It argues that efforts to promote women's empowerment should recognise that empowerment requires women to make their own strategies to suit their particular circumstances. A conceptualisation of empowerment is proposed and this framework consists of 4Cs (capability, confidence, choice, commitment) and 3As (awareness, achievement, acknowledgment). The 4Cs and 3As reflect the personal, relational, and multidimensional aspects of empowerment. The framework talks uniquely to the context where women in this study live, and particularly how they engage in an empowerment project.